2018
DOI: 10.1002/joc.5705
|View full text |Cite
|
Sign up to set email alerts
|

Using multi‐model ensembles of CMIP5 global climate models to reproduce observed monthly rainfall and temperature with machine learning methods in Australia

Abstract: Global climate models (GCMs) are useful tools for assessing climate change impacts on temperature and rainfall. Although climate data from various GCMs have been increasingly used in climate change impact studies, GCMs configurations and module characteristics vary from one to another. Therefore, it is crucial to assess different GCMs to confirm the extent to which they can reproduce the observed temperature and rainfall. Rather than assessing the interdependence of each GCM, the purpose of this study is to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 49 publications
3
89
0
Order By: Relevance
“…Ensemble simulation is estimated by averaging the predictions of all trees, which is considered as the final simulation. Wang et al (2018) and reported that the performance of RF varies with the number of trees (n tree ) and the number of variables randomly sampled (m try ) at each split in developing the trees. In those studies, it was observed that RF performance increases with the increase in the value of ntree.…”
Section: The Classification and Regression Tree (Cart) Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…Ensemble simulation is estimated by averaging the predictions of all trees, which is considered as the final simulation. Wang et al (2018) and reported that the performance of RF varies with the number of trees (n tree ) and the number of variables randomly sampled (m try ) at each split in developing the trees. In those studies, it was observed that RF performance increases with the increase in the value of ntree.…”
Section: The Classification and Regression Tree (Cart) Techniquementioning
confidence: 99%
“…Salman et al (2018a) generated the MME mean for maximum and minimum temperature over Iraq using four CMIP5 GCMs and reported that RF-based MME performed better compared to individual GCMs. Likewise, Wang et al (2018) conducted a comprehensive study to evaluate the performance of different machine learning techniques including RF, a support vector machine, Bayesian model averaging, and the arithmetic ensemble mean in generating MMEs. They considered 33 CMIP5 GCMs for precipitation and temperature over 108 stations located in Australia and concluded that RF and SVM can generate better-performing MMEs compared to other techniques.…”
Section: Multi-model Ensemble (Mme) Meanmentioning
confidence: 99%
See 2 more Smart Citations
“…generated MME mean for maximum and minimum temperature over Iraq using four CMIP5 GCMs and reported RF performed better compared to individual GCMs. Likewise,Wang et al (2017) conducted a…”
mentioning
confidence: 99%